﻿Revision of the family Milacidae from Switzerland (Mollusca, Eupulmonata, Parmacelloidea) - Vivianne M. Schallenberg; René Heim; Ulrich E. Schneppat; Peter Müller; Jörg Rüetschi; Eike Neubert (ZooKeys, 2022)
In this work, the presence of species of the slug family Milacidae in Switzerland was investigated by using the barcoding marker cytochrome c oxidase subunit I (COI) as well as traits of the body and the genital organs. Currently, three species of Tandonia living in Switzerland in established populations could be reported, i.e., T. rustica, T. budapestensis, and T. nigra. The three records of Milax gagates were re-investigated, but only for one of these records could the identification be reconfirmed. This species has currently no established and thriving population in Switzerland. For all species recorded, detailed descriptions of body morphology, genital anatomy, and distribution data are provided based on the investigated Swiss animals. An unknown pale colour morph of a Tandonia sp. from Canton Ticino could be identified as T. nigra, and the barcodes of T. nigra specimens were submitted to GenBank for the first time. The identity of the Italian and Austrian populations of T. nigra from the Bergamasque Alps and north Tirol is evaluated. Observations on details of the morphology of the genital organs in T. rustica vs. T. kusceri are discussed.